(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize evidence on the efficacy and safety of oral Passiflora incarnata in adults with insomnia or sleep-related complaints. Methods: This was a structured narrative review. PubMed, Scopus, Web of Science, and Google Scholar were searched from January 2020 to November 2025. Eligible studies were randomized controlled trials in adults evaluating oral passionflower monotherapy for at least 1 week and using standardized sleep measures. Mechanistic and safety references were used to contextualize the findings. Results: Three eligible trials were included in the qualitative synthesis. Overall, Passiflora incarnata showed mild to moderate benefits in total sleep time, sleep efficiency, and subjective sleep quality. One placebo-controlled polysomnographic study reported increased total sleep time after 2 weeks. A 2024 trial in adults with stress-associated insomnia showed improved sleep and reduced perceived stress. A 2025 study found that passionflower remained beneficial, although it was less effective than chamomile on some outcomes. Passionflower was generally well tolerated. Conclusion: Oral Passiflora incarnata may be a relatively safe adjunctive option for mild to moderate insomnia, particularly when associated with stress or anxiety. However, current evidence remains insufficient to support its routine use as stand-alone therapy.